Dino rib ticklers hugely funny jokes about dinosaurs - Dahl, Michael; Reibeling, Brandon (Minneapolis Picture Window Books, 2003)
An easy-to-read collection of riddles about raptors, triceratops, and other dinosaurs.
0470
Keywords: Dinosaurs; Wit and humor -- Juvenile; Riddles; Jokes